Microbiological assessment of freshly-fried home-made and commercial fish balls in Miagao, Iloilo. - Develos, Kristel Ann Dionzon
Two-types of fish balls, home-made and commercial, were collected from the three selected sources in Miagao, Iloilo specifically, the town center (location A), public market area (Location B) and the College of Arts and Sciences (CAS) compound in UP Visayas (Location C). Samples were subjected to microbiological analyses, specifically, total plate (TPC), Most Probable Number (MPN) of fecal coliform and detection of the specific pathogens Salmonella and E.coli. Physico-chemical tests, namely, hydrohen ion concentration (pH) and water activity (aw) were also conducted. The range of mean TPC for home-made fish balls from all three-selected sources in the three sampling periods were 2.64 x 104 to 5.8 x 107 cfu/g. Kruskal-Wallis Test at α= 0.05 showed that the microbial quality of home-made fish balls from the three selected sources had no significant difference. Fecal coliform and E.coli were detected to be present at unsatisfactory levels while Salmonella was not detected in all locations. On the other hand, the range of mean TPC for commercial fish balls from the three selected sources were 2.82 x 104 to 1.32 x 106 cfu/g. Kruskal Wallis Test at α= 0.05 in the mean TPC of the three selected sources had no significant difference. Fecal coliform and E.coli were detected to be present at unsatisfactory levels in all sampling periods while Salmonella was also not detected in all sampling periods. Mann-Whitney U-Test shows that there was no significant difference between the mean TPC of home-made and commercial fish balls. The pH range of the home-made fish balls from the three selected sources was 6.59 to 7.23. Kruskall Wallis Test at α= 0.05 level of significance showed that there was no significant difference among the three locations. The mean water activity values ranging from 0.909 to 0.937 also showed no difference. The pH range of the commercial fish balls from the three selected sources was 4.58 to 4.95 and had no significant difference among the locations. Mann-Whitney U-Test indicated that there was a significant difference between both home-made and commercial fish balls in terms of pH value. Likewise, Mann-Whitney U-Test for water activity (aw) revealed significant difference between home-made and commercial fish balls. The Total Plate Count (TPC) of the home made fish balls was unsatisfactory and the commercial fish balls was acceptable in comparison to the White Salmonella was absent from the food samples, E. coli was detected and fecal coliform levels of the home-made and commercial fish balls were both unsatisfactory. The presence of certain pathogens in the samples indicate that home-made and commercial fish balls sold in the selected sources may be considered risky for consumption.